La gestión de aula en la formación profesional integral - López Rodríguez, José Fernando (2025)
Classroom management involves a set of teaching actions that allow us to build an appropriate climate for learning, but also focus the purposes of teaching on the training of more humane people. Therefore, this essay aims to generate discussion about the preparation of teachers and their educational responsibility to address the challenges that future professionals face. To this end, the text is developed in three sections under the analytical and interpretive exercise of theories about: the purposes of a good classroom management, its impact on the comprehensive training of future professionals and the impediments that stopped their educational process. To the extent that teachers, society and the State are in congruence with the real principles of education, classroom management can attend to the human in a committed and responsible manner with the environment, with culture, with diversity and with coexistence. For their part, those who teach must make a full dedication of their being, which implies constant preparation and passion for educating. It is concluded that the comprehensive training of future professionals through adequate classroom management contributes to academic success, the development of essential skills for life and the transformation of social realities such as interpersonal relationships, empathy, emotional intelligence, teamwork and critical thinking.